Pengaruh Customer Satisfaction Dan Customer Experience Terhadap Revisit Intention Di Fave Hotel Olo Padang - Raymundus Samosir; Dwi Pratiwi Wulandari (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
The research was done against the background of low level of guest intention to revisit to Fave Hotel Olo Padang. This research is included in causal associative with methods by survey. The research data were obtained by questionnaires distributed to 204 samples from 2001 population. Then the processing for data use means of data metabulation and data description using the SPSS program. The results shownthat the overall Customer Satisfaction variable in category in good with a score of 50,0%, the overall Customer Experience variable in category as good with a score of 77,4%. And the overall Revisit Intention variable is categorized as good with a percentage of 60,29%. There is a contribution of Customer Satisfaction (X1) and Customer Experience (X2) to Revisit Intenton, namely at 44.3% but the remaining 55.07% gets influence from other factors